Effects of training on sand or hard surfaces on sprint and jump performance of team-sport players: a systematic review with meta-analysis - Pereira, L. A.; Freitas, T. T.; Marín-Cascales, E.; Bishop, C.; McGuigan, M. R.; Loturco, I. (Strength and Conditioning Journal, 2021)
We examined the effectiveness of training on sand and compared the effects of sand and hard surface training programs on the sprint and jump performance of team-sport players. PubMed MEDLINE, SPORTDiscus, and Web of Science databases were used in the literature search. A total of 377 records were initially identified, and 6 studies comprising 136 athletes were included in the meta-analysis. Precomparisons and postcomparisons showed that sand training interventions were effective at improving both jump and sprint capacities. When comparing sand and hard surfaces, no significant differences in favor of any of the interventions were observed. In summary, this review revealed that sand training is an efficient strategy to improve jump and sprint performances in team-sport players. Moreover, sand surfaces produced similar gains to those observed after hard surface training schemes. Strength and conditioning coaches and sport scientists who work with team sports can use both sand and hard surface training programs as part of their regular training practices, during distinct phases of the season.